Participação das escolas secundárias de Santos nos campeonatos colegiais: prática de educação física escolar (1934-l964) - Souza, Felipe Amorim de (2012)
Sport is a vital activity in Santos, it is also part of its history since the city has won the Jogos Abertos do Interior (Interior¿s Open Games) state championship several times. This tradition has its origins in the late 19th century, when airs of modernity and wealth generated from the coffee trade invaded the city, transforming its economy, urban aspects and social interaction as the first rowing clubs started to appear. These informal associations abounded before the city¿s first high-rises were built. Santos breathed sports not only in its clubs, lowland fields and beaches, but also in its schools. Since the early 20th century, the skills and innovative methods of the city¿s physical education teachers caught people¿s attention. The work of these masters, their pedagogical input, contributed to the city¿s cultural development. Their dedication to sport activities and civic parades had a great impact on society. This study seeks to uncover part of the history of school competitions in the city of Santos in the 20th century (1934-1964) by understanding how these sport events took place, and revealing the main figures behind them and their goals. This study was guided, mainly, by the reflections of Marcus Aurélio Taborda de Oliveira, published in his thesis for PUC-SP entitled A Revista Brasileira de Educação Física e Desportos (1968-1984) e a experiência da rede municipal do ensino de Curitiba: entre adesão e a resistência (The Brazilian magazine of physical education and sports ¿ 1968-1984 ¿ and the experience of Curitiba City Public Schools: between accession and resistance), a work that allows an understanding of the national physical education and its main achievements; and those made by Eliana Campos Prates in her dissertation, defended in 2009 for a master¿s degree in Education at Universidade Católica de Santos, that offers an historical analysis of Santos¿ school sport addressing women¿s teams and the emancipation of women through physical practices. The methodological approach utilized in this study was documentary research, mainly newspaper articles, iconographic sources and oral history, obtained through interviews with former teachers and access to their personal archives. Also of great relevance was the material found at the Centro da Memória Esportiva Museu De Vaney (Center of Sport Memory De Vaney Museum), in Santos. The study led to the conclusion that the sport practices of school physical education were dictated by official education policies and developed by teachers of the discipline with quality education in the field. To the school sport youth, values were transmitted regarding order, discipline, spirit of initiative and social skills in a healthy competitive environment. The sport context of this city by the beach was a fertile soil, and its clubs had, in the local schools, their greenhouse.